Comparison of the efficacy and safety of first-line treatments for of advanced EGFR mutation-positive non-small-cell lung cancer in Asian populations: a systematic review and network meta-analysis - Chen, Wei; Miao, Julian; Wang, Ying; Xing, Wenzhong; Xu, Xiumei; Wu, Rui (Frontiers in Pharmacology, 2023)
Background: According to the 2023 guidelines for treating non-small-cell lung cancer (NSCLC), first-line treatment and recently developed agents for the treatment of epidermal growth factor (EGFR) mutation-positive locally advanced or metastatic NSCLC were compared in this meta-analysis. Treatment regimens involved in the included studies included first, second, and third-generation tyrosine kinase inhibitors (TKIs), TKIs plus chemotherapy, TKIs plus angiogenesis inhibitors, and platinum-containing doublet chemotherapy with or without bevacizumab. Considering the varying efficacy and safety of drugs in people of different ethnic origins, the optimal regimen should be determined, and the safety of first-line treatments should be assessed in the Asian population specifically. Methods: PubMed, Embase, the Cochrane Library, Web of Science, and the China National Knowledge Infrastructure (CNKI) were systematically searched to retrieve reports on randomized controlled trials (RCTs) with research data published from inception to 1 February 2023. Adopting Asian patient populations as the target (including studies in which Asian patients accounted for more than 50% of the sample), a network meta-analysis (NMA) was conducted for comparison of treatment regimens and treatments were ranked based on the surface under the cumulative ranking curve (SUCRA). Results: A total of 19 RCTs involving 5,824 patients and covering 14 treatment regimens were included. The primary outcome measure examined in this study was progression-free survival (PFS); other outcome measures examined were overall survival (OS), disease control rate (DCR), objective response rate (ORR), occurrence of any adverse events (AE), occurrence of adverse events of grade 3 or above (≥3AE), and occurrence of serious adverse events (SAE). In terms of PFS, all regimens including TKIs (as a monotherapy or in combination with other therapies), as well as bevacizumab (Bev) plus chemotherapy (Ch) were found to be significantly superior to basic chemotherapy (HRs: 0.09–0.61, p < 0.05 in all cases compared with Ch alone). The highest-ranking therapies were erlotinib (Erl) plus Bev (SUCRA: 0.94) and Erl plus ramucirumab (Ram) (SUCRA: 0.93). Regarding OS, no significant differences was observed between first-line treatment strategies; the top four treatments based on SUCRA, in rank order, were Bev + Ch (0.87), gefitinib (Gef) plus Ch (0.81), dacomitinib (Dac) (0.79), and osimertinib (Osi) (0.69). Additionally, there were no significant differences between first-line treatment strategies in terms of DCR. Regarding ORR, the top three treatments based on SUCRA were Erl + Bev (0.85), Erl + Ram (0.76), and Gef + Ch (0.74). No significant difference between first-line treatment strategies was observed in terms of the risk of AE. However, based on SUCRA, Erl ranked highest on avoidance of ≥ 3AE (0.97), and Osi ranked highest on avoidance of SAE (0.91). Conclusion: Based on these analyses of survival benefits, tumor burden response, and safety, furmonertinib (Fur), Osi, and aumolertinib (Aum) may represent the best treatment regimen options for Asian patients, significantly prolonging survival (as measured by median PFS/OS), eliciting a greater tumor burden response, and exposing patients to a lower risk of adverse events. Although Erl + Bev and Erl + Ram are associated with the best survival benefits in terms of PFS, further clinical studies are still needed to identify ways to reduce the risk of adverse events. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php? ID=CRD42023407994, identifier CRD42023407994